A comparative analysis of single-port and four-port laparoscopic cholecystectomies in patients with chronic calculous cholecystitis - Kravchenko, B. S.; Klymenko, V. M.; Kravchenko, S. M.; Zakharchuk, A. V.; Тumanska, N. V.; Кравченко, Борис Сергійович; Клименко, Володимир Микитович; Кравченко, Сергій Михайлович; Захарчук, Олександр Валентинович; Туманська, Наталя Валеріївна (My University, 2019)
The objective: To conduct a comparative analysis of the results of single-port and four-port laparoscopic cholecystectomies in patients with chronic calculous cholecystitis. Materials and methods. During 2015 – 2017 years 214 patients underwent surgery for chronic calculous cholecystitis. All patients were divided into 2 groups. The first group consisted of 102 (47.6%) patients, who underwent single-port laparoscopic cholecystectomy (SILC). The second included 112 (52.3%), for whom standard laparoscopic cholecystectomy was performed. The results in both groups were compared on the following criteria: 1) patient characteristics: age, sex and body mass index (BMI); 2) the duration of surgical intervention; 3) the total time of the patient hospitalisation; 4) the presence of drainage in the abdominal cavity; 5) anaesthetic assessment of the patient's physical condition prior to surgical intervention (classification of ASA); 6) the level of pain within 6 hours after the operation – visual analogue scale (VAS; from 0 to 10, where 0 – no pain, 10 – maximum pain); 7) the necessity for the administration of opioid analgesics in the postoperative period; 8) the presence of complications arose during surgery (bleeding, injury of the common bile duct, gallbladder perforation, leak of bile into the abdominal cavity); 9) the postoperative quality of life, cosmetic outcome (evaluation was performed using the 4-Likert scale.
Keywords: single-port access; laparoscopic cholecystectomy; cholelithiasis; chronic calculous cholecystitis